Idiopathic pulmonary hemosiderosis as an occupational disease: a clinical case - Raznatovska, О. М.; Gumeniuk, G. L.; Yasinskyi, R. M.; Fedorec, A. V.; Разнатовська, Олена Миколаївна; Гуменюк, Г. Л.; Ясінський, Роман Миколайович; Федорець, Андрій Васильович (My University, 2023)
BACKGROUND. Idiopathic pulmonary hemosiderosis (IPH) in adults is a rare pathology of unknown etiology. We did not find information about IPH in adults with occupational hazards in the available literary sources, which makes this work relevant. OBJECTIVE. To analyze the peculiarities of the IPH course in a patient with 23 years’ experience as a gas-electric welder at factories by our own clinical observation. RESULTS AND DISCUSSION. Changes in the form of heterogeneous pneumatization of the lung parenchyma due to the increased interstitial component were determined on the computer tomography of the chest cavity (CT of the chest cavity) 1.5 years before the patient’s visit, but no additional examination was prescribed, and only the diagnosis “Chronic obstructive pulmonary disease” (COPD) was made. Negative dynamics due to the increase of miliary nodular dissemination of the lungs was revealed on the CT scan of the chest after 1.5 years. IPH was already detected pathohistologically after videothoracoscopy of the right lung with biopsy. Shortness of breath and cough increased in the patient, but apart from treatment aimed at COPD treating, no other therapy was prescribed (this therapy did not have a positive effect). The patient underwent a comprehensive immunological examination: the indicators of the anti-neutrophil cytoplasmic antibodies (ANCA) profile and the complex immunological blood test were within the normal range, which ruled out pulmonary vasculitis and an immune-mediated process. Considering the positive Quantiferon test, the patient was examined and the tuberculosis was excluded. Patient have not been suffered from hemoptysis and anemia from the moment of detection of the first changes on the CT scan of chest up to the present time. Due to treatment, the clinical and radiological stabilization of the process was determined after 4 months: the clinical symptoms of the disease decreased; small nodular shadows with areas of fibrosis, which are characteristic of the period of remission, were determined on the CT scan of the chest. ОБҐРУНТУВАННЯ. Ідіопатичний гемосидероз легень (ІГЛ) у дорослих – це рідкісна патологія невідомої етіології. У доступних літературних джерелах ми не знайшли даних щодо розвитку ІГЛ у дорослих осіб із професійними шкідливостями, що робить цю роботу актуальною. МЕТА. На власному клінічному спостереженні проаналізувати особливості перебігу ІГЛ у пацієнта з 23-річним стажем роботи газоелектрозварювальником на заводах. РЕЗУЛЬТАТИ ТА ЇХ ОБГОВОРЕННЯ. За 1,5 року до звернення в пацієнта визначалися зміни на комп’ютерній томограмі органів грудної порожнини (КТ ОГП) у вигляді неоднорідної пневматизації паренхіми легень через посилений інтерстиціальний компонент, але додаткового дообстеження призначено не було, а встановлено лише діагноз «Хронічне обструктивне захворювання легень» (ХОЗЛ). Через 1,5 року на КТ ОГП виявлено негативну динаміку внаслідок наростання міліарної вузликової дисемінації легень. Після відеоторакоскопії правої легені з біопсією патогістологічно вже було виявлено ІГЛ. У пацієнта наростали задуха та кашель, але крім лікування ХОЗЛ, яке не мало позитивного ефекту, іншої терапії не призначалося. Пацієнту було проведено комплексне імунологічне дообстеження: показники ANCA-профілю та комплексного імунологічного дослідження крові виявилися в межах норми, що виключило легеневі васкуліти й імуноопосередкований процес. Зважаючи на позитивний квантифероновий тест, пацієнт був дообстежений, і туберкульозний процес було виключено. Із часу виявлення перших змін на КТ ОГП і дотепер у пацієнта не визначалися кровохаркання й анемія. На тлі лікування через 4 місяці спостерігалася клінічно-рентгенологічна стабілізація процесу: зменшилися клінічні прояви захворювання, на КТ ОГП визначалися дрібновузликові тіні з ділянками фіброзу, які характерні для періоду ремісії.
Ідіопатичний гемосидероз легень як професійне захворювання: клінічний випадок
Keywords: idiopathic pulmonary hemosiderosis; occupational disease; ідіопатичний гемосидероз легень; професійне захворювання